El juego-trabajo y su importancia en el desarrollo de la diversidad cultural en los niños de educación básica de la unidad educativa” Dr. Gabriel García Moreno - Altamirano Álvarez, Mercedes Catalina (2022)
ABSTRACT: Interculturality is a permanent and dynamic process, between relationships, the community and the learning of cultures in conditions of respect, mutual legitimacy. Based on the recognition of the diversity of cultures, worldviews and interpretations of reality. That is why this research aimed to determine the importance of play-work in the development of cultural diversity in children in the first year of Basic Education of the Educational Unit "Dr. Gabriel García Moreno school year 2020-2021. The methodology that was used has a non-experimental design, with an inductive, qualitative, propositional, field, transversal and descriptive model, the techniques that were used were the structured observation and the survey, the instruments the observation sheet and the questionnaire, the population was 25 boys and girls, 25 parents and 30 teachers; Through the analysis of the results, it was possible to conclude that play - work is important in the development of cultural diversity, because through the learning corners, and the application of games, didactic and technological tools, the students better assimilate the new knowledge, as well as they are able to identify and learn about the customs and traditions that are developed in the locality.